KAIPAD –a Unique, Naturally Organic, Saline Prone Rice Ecosystem of Kerala, India, - T. Vanaja (American Journal of Environmental Protection., 2013)
A complex and ecologically responsive rice-fish farming system has evolved in the coastal wetland regions of India over centuries. Kaipad is a unique coastal wetland rice production tract which is saline prone and naturally organic production tract of North Kerala, India which was not much known to the scientific world. The rice produce from this par- ticular ecosystem is purely organic. Apart from integrated organic farming system in which rice cultivation and aquaculture go together, Kaipad ecosystem is featured with rich biodiversity of flora and fauna, organically rich soil, mangroves, and migratory birds. The Pokkali tract of south Kerala is said to be synonymous to Kaipad tract of North Kerala. But soils of Kaipad slightly differ from that of Pokkali. Rice farming in Kaipad is carried out in a peculiar way, purely in a natural way relying on the monsoon and the sea tides. Besides its own saline tolerant land races of rice, recently high yielding rice va- rieties were developed for Kaipad tract by Kerala Agricultural University utilizing the traditional land races. Even though the product from Kaipad is purely organic ,nothing much has been done to explore the value of organic rice for the benefit of farmers. Besides research accomplishment, a comprehensive multi faced development approach is necessary to preserve, protect and develop this unique organic rice bowl of Kerala, governed by small and marginal farmers.